TINJAUAN PERSEPSI MANAJEMEN TERHADAP STRUKTUR MODAL PERUSAHAAN "GO PUBLIC" - Farah Margaretha (Media Riset Bisnis & Manajemen, 2003)
This survey examines (1) manager perception about capital structure at listed company, (2) correlation between type of industry and the factors that influenced capital structure. This study used question aire and depth interview to 50 CFO listed company in Jakarta stock exchange the result of the study found that the significant factor that influenced capital structure are growth of sales, sales stability, finanaal structure and tax.